2021
DOI: 10.3390/agronomy11071319
|View full text |Cite
|
Sign up to set email alerts
|

One-Time Acidification of Slurry: What Is the Most Effective Acid and Treatment Strategy?

Abstract: Acidification of slurry is a common practice to reduce ammonia and methane emissions. Sulfuric acid is usually used for this process. However, this has been criticized due to the high sulfur input into soils. Therefore, the objective of this study is to show the effectiveness of a one-time acidification with alternative acids also in combination with other treatment strategies. The amount of acid as well as the change of pH value during storage were investigated. For most variants, a strong pH increase occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The results indicated that changing the acidity of pig slurry can result in biochemical changes that reduce the formation of certain gases. In other words, acidity is used to create less favorable conditions for the bacteria and enzymes that contribute to NH 3 and H 2 S formation during storage (Overmeyer et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that changing the acidity of pig slurry can result in biochemical changes that reduce the formation of certain gases. In other words, acidity is used to create less favorable conditions for the bacteria and enzymes that contribute to NH 3 and H 2 S formation during storage (Overmeyer et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The process of manure acidification, where sulfuric or other similar acids are introduced into manure, effectively reduces ammonia emissions, a significant environmental concern in dairy farming. By lowering the pH, this technique inhibits the volatilization process of ammonia, thereby curtailing its release into the atmosphere [78][79][80][81][82]. Moreover, acidified manure presents added benefits for soil health, particularly in enhancing nutrient retention and availability.…”
Section: Acidification Of Manure For Ammonia Emission Reductionmentioning
confidence: 99%
“…Petersen et al 12 observed a gradual increase of pH from acidified cattle from 4.5 to 6 in a 3-month study. Overmeyer et al 48 investigated the stability of pH in acidified slurry and reported that only acidification to pH 3.0 allows a long-term reduction due to the reduction of degradation of VFA and mineralization of organic nitrogen. However, Fangueiro et al 49 observed a stable pH during the storage period after acidification of cattle slurry to pH 5.5 with no further addition of fresh slurry.…”
Section: Full-scale Slurry Storagementioning
confidence: 99%